2023
DOI: 10.1111/1750-3841.16782
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, chemical profiles, antioxidative activities, and angiotensin‐converting enzyme 2 inhibitory effect of date fruit vinegar

Minmin Tang,
Zhihuang Wang,
Jiaxin Luo
et al.

Abstract: Date palm (Phoenix dactylifera L.) is an important commercial crop extensively consumed as a staple food and has been applied in many ethnomedical systems. Fruit vinegar is a preservative, condiment, and beverage with a spectrum of health benefits. Studies about the preparation, chemical profiles, and bioactivities of date fruit vinegar (DFV) are fundamental requirements for industrialization production. This study focused on the lab‐scaled producing conditions, chemical profiles of DFV, and its bioactivities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
0
0
Order By: Relevance
“…The three-dimensional graph of the modeling (Figure ) shows the increases. Vinegar has a wide range of physiological functions, including antihypertensive effects, as proven by many studies . It was found that the interactions (two-way) were statistically significant.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The three-dimensional graph of the modeling (Figure ) shows the increases. Vinegar has a wide range of physiological functions, including antihypertensive effects, as proven by many studies . It was found that the interactions (two-way) were statistically significant.…”
Section: Resultssupporting
confidence: 89%
“…Vinegar has a wide range of physiological functions, including antihypertensive effects, as proven by many studies. 36 It was found that the interactions (two-way) were statistically significant. The findings were like those outlined by Onyeaka et al ( 2023), who saw an increase in total flavonoid, phenolic content, and antioxidant capacity in sonicated samples, with variations in exposure duration and frequency.…”
Section: Optimization Of Poppy Vinegar For Acementioning
confidence: 96%